DESAIN PENGEMBANGAN RUANG PUBLIK TERPADU RAMAH ANAK (RPTRA) DI KOMPLEKS KANTOR KELURAHAN KRAMATJATI JAKARTA TIMUR - Margareta Maria Sudarwani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
In the Kramatjati Sub-District Office Complex, there is an Integrated Child-Friendly Public Space (RPTRA) built on a vacant land formerly occupied by a soy sauce factory. RPTRA Mustika Kramatjati has successfully revitalized the area, preventing urban decay that could lead to the emergence of slums, abandonment, and increased crime rates. However, due to population growth, this RPTRA faces limitations in accommodating activities, and its densely packed schedule leads to insufficient maintenance. Therefore, redesign or reengineering is necessary to make this RPTRA more effective in facilitating community activities and providing comfort. In this collaborative program, The Faculty of Engineering of Architecture UKI partners with stakeholders to propose a redesign of RPTRA as the primary solution to address these issues. It is hoped that this Community Service Team can make a tangible contribution to optimizing the RPTRA's function in accordance with the established RPTRA Management Guidelines. This initiative involves field observations, data collection, design presentations to stakeholders, and engages professors and students from the Architecture Program at the Faculty of Engineering, Universitas Kristen Indonesia, as a contribution to the community in the field of architecture.